Lactobacillus pentosus Increases the Abundance of Akkermansia and Affects the Serum Metabolome to Alleviate DSS-Induced Colitis in a Murine Model - Ma, Yong; Hu, Chao; Yan, Wenxin; Jiang, Hongmei; Liu, Gang (Frontiers in Cell and Developmental Biology, 2020)
Lactobacillus pentosus has the beneficial function of regulating the host’s immune system and plays an indispensable role in intestinal health. The purpose of this study was to investigate the specific mechanism by which L. pentosus relieves dextran sulfate sodium (DSS) induced ulcerative colon inflammation. We randomly divided 24 mice into three groups, which were administered either a basic diet, drinking water with 2.5% DSS (DSS), or drinking water with 2.5% DSS and intragastric administration of L. pentosus (DSS + L. pentosus). DSS was added to the drinking water on days 8 to 12, and L. pentosus was administered on days 12 to 19. Serum was collected for metabolomic analysis, colon length and weight were measured, and colon contents were collected to detect microbial structural composition. Compared with the DSS group, the DSS + L. pentosus group had significantly higher levels of indolepyruvate and pantothenic acid in the serum and significantly lower levels of 3,4-dimethyl-5-pentyl-2-furannonanoic acid and 5-oxo-6-trans-leukotriene B4. Moreover, compared with the other two groups, the DSS + L. pentosus group had a significantly greater abundance of Akkermansia. The abundance of Akkermansia was positively correlated with indolepyruvate and pantothenic acid levels. Therefore, L. pentosus can interact with Akkermansia to increase its abundance in the intestinal tract. This results in the production of metabolites that are beneficial for the regulation of intestinal immunity, thereby alleviating DSS-induced ulcerative colon inflammation.